A táblás csokoládé vásárlói magatartását befolyásoló tényező elemzése a kapuvári Spar szupermarketben - Vörös Henrietta (2016)
I have chosen „table chocolates” as topic of my thesis, because owing to its popularity re-spectively its extensive usability it has a lead in the commerce. The subject of my interest and the mark of my research is to know the shopping habits in case of the table chocolates and to know how the customers decide (brand, package, taste, quality, price, presentation) when selecting a product at the SPAR supermarket in Kapuvár. The main target of my research is to observe in what proportion the customers consume table chocolates at the SPAR supermarket in Kapuvár, and whether they buy it at this shop. Besides I was eager to know if the consumers select the brand label or the private label in case of the table chocolates. I have carried out two researches, the one is the secondary research, that serves a good base but gives not enough information. Therefore, I collected information about the con-sumption and the distribution of the chocolate in Hungary. The other is the primary re-search, which consist of a questionnaire with 11 questions + 4 scores about demography, that includes closed questions. I tried to do the analysis so that it represents the reality. As the result of my research I have drown the inference that table chocolate is bought at the SPAR supermarket by the women between the age of 40-49, who have average income, and are satisfied with the lineup of the supermarket. The consumers buy the chocolates for their own consumption for noshery on a monthly basis. The costumers prefer the choco-lates of the brand label and most of them consume milk chocolate. The price and the taste is authoritative for the consumers when selecting table chocolates. In my opinion my research has reached its target, because it reveals what are the aspects of the consumers when selecting chocolate. A szakdolgozatom témájának azért választottam a táblás csokoládét, mert népszerűsége, illetve széleskörű felhasználhatósága miatt a kereskedelemben vezető szerepet tölt be. Az érdeklődésem tárgya és a kutatásom célja, hogy megismerjem a táblás csokoládé vásárlási szokásait, illetve, hogy mi alapján döntenek a vásárlók a kapuvári SPAR áruházban (márka, csomagolás, íz, minőség, ár, kiszerelés) egy termék kiválasztásakor. A kutatásom fő célja, hogy megfigyeljem, a kapuvári SPAR szupermarketben vásárlók milyen arányban fogyasztanak táblás csokoládét, és azt ebben az üzletben vásárolják-e. Ezen kívül kíváncsi voltam arra is, hogy a fogyasztók a gyártói márkás táblás csokoládékhoz vagy a kereskedelmi márkás táblás csokoládékhoz nyúlnak leginkább. Kétféle kutatást végeztem el, az egyik a szekunder kutatás, ami jó alapot szolgál, de nem nyújt kellő információt. Tehát ennek keretében információt gyűjtöttem a csokoládé fogyasztásáról, illetve megoszlásáról Magyarországon. Másik a primer kutatás, ami 11 kérdésből álló kérdőív + 4 a demográfiai, ami zárt kérdéseket tartalmaz. Az elemzést igyekeztem úgy elkészíteni, hogy reprezentálja a valóságot. A kutatásom végeredménye-ként, azt a következtetést tudtam levonni, hogy a kapuvári SPAR áruházban a táblás csokoládét leginkább a 40-49 éves nők vásárolják átlag jövedelemmel, valamint elégedettek a szupermarket által kínált felhozatallal. A fogyasztók saját fogyasztásra vásárolják a csokoládékat nassolás céljából, havi rendszerességgel. A vásárlók a gyártói márkás csokoládét részesítik előnyben és többségük a tejcsokoládét fogyasztja. Táblás csokoládék kiválasztásakor a fogyasztó számára az íz és az ár a mérvadó. Véleményem szerint kutatásom elérte célját, mivel rávilágított arra, hogy a fogyasztók milyen szempontok alapján választanak csokoládét.